On properties of the solutions of the Weber equation - Trukhan, Yu.S. (Carpathian Mathematical Publications, 2015)
Growth, convexity and the $l$-index boundedness of the functions $α(z)$ and $β(z)$, such that $α(z^4)$ and $zβ(z^4)$ are linear independent solutions of the Weber equation $w''-(\frac{z^2}4- u-\frac12) w=0$ if $ u=-\frac12$ are investigated.